2020
DOI: 10.14416/j.asep.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Severity Estimation of Plant Leaf Diseases Using Segmentation Method

Abstract: Plants have assumed a significant role in the history of humankind, for the most part as a source of nourishment for human and animals. However, plants typically powerless to different sort of diseases such as leaf blight, gray spot and rust. It will cause a great loss to farmers and ranchers. Therefore, an appropriate method to estimate the severity of diseases in plant leaf is needed to overcome the problem. This paper presents the fusions of the Fuzzy C-Means segmentation method with four different colour s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The integration of these techniques leads to a noteworthy improvement of 5.86% in solution quality compared to individual segmentation approaches. Notably, this represents the first instance wherein image segmentation has been shown to significantly enhance the accuracy of the proposed model, aligning with previous works [62][63][64][65][66], which also affirm the efficacy of image segmentation in enhancing model accuracy across various applications.…”
Section: Advancing Leaf Disease Classification In Cau: a Meta-learner...supporting
confidence: 86%
“…The integration of these techniques leads to a noteworthy improvement of 5.86% in solution quality compared to individual segmentation approaches. Notably, this represents the first instance wherein image segmentation has been shown to significantly enhance the accuracy of the proposed model, aligning with previous works [62][63][64][65][66], which also affirm the efficacy of image segmentation in enhancing model accuracy across various applications.…”
Section: Advancing Leaf Disease Classification In Cau: a Meta-learner...supporting
confidence: 86%
“…A maximum mean accuracy of 99% is achieved using the Bagged tree (BT) classifier using color features compared to the other classifiers (KNN, SVM, Complex Tree, and BT). Fuzzy C-Means clustering-based segmentation is used to segment the diseased location in corn leaves [ 17 ]. They have used the Plant Village image dataset for developing their model to identify three different types of diseases in corn leaf such as blight, gray spot, rust, and normal leaf.…”
Section: State-of-the-art Work Related To Leaf Disease Detectionmentioning
confidence: 99%
“…Entuni et al [52] also computed the severity of the disease in plant leaves by combining Fuzzy C-Means and YCbCr colour space. It was concluded that YCbCr colour space has a greater detection rate when compared with RGB, HSV, 𝐿 * 𝑎 * 𝑏, as YCbCr can separate luminance from chrominance more effectively.…”
Section: -2-role Of Image Segmentationmentioning
confidence: 99%
“…The proposed method uses K-means clustering to separate the diseased lesion, from which the affected ratio is calculated to predict the severity. K-means algorithm performed on km-ADDS is as follows [52,[58][59][60][61]: K=3 is used in the proposed model. Figure 11 shows the segmentation results and the different steps involved in segmentation of the diseased spot from the cropped image using K-means via applying the algorithm.…”
Section: -1-2-image Segmentation and Severity Estimationmentioning
confidence: 99%